Buzzwords in females' ears? The use of buzz songs in the communication of nightingales (Luscinia megarhynchos). - Michael Weiss (Public Library of Science (PLoS), 2012)
Differences in individual male birds' singing may serve as honest indicators of male quality in male-male competition and female mate choice. This has been shown e.g. for overall song output and repertoire size in many bird species. More recently, differences in structural song characteristics such as the performance of physically challenging song components were analysed in this regard. Here we show that buzz elements in the song of nightingales (Luscinia megarhynchos) hold the potential to serve as indicators of male quality and may therefore serve a communicative function. Buzzes were produced with considerable differences between males. The body weight of the males was correlated with one measure of these buzzes, namely the repetition rate of the buzz subunits, and individuals with larger repertoires sang buzzes at higher subunit-rates. A model of buzz performance constraints suggested that buzzes were sung with different proficiencies. In playback experiments, female nightingales showed more active behaviour when hearing buzz songs. The results support the idea that performance differences in the acoustic fine structure of song components are used in the communication of a large repertoire species such as the nightingale.